The Effectiveness of Learning English Using LMS Google Classroom during Covid-19 Pandemic - Muhammad Taufik; Andi Samsu Rijal; Dahniar Dahniar; Eka Apriani (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aimed to determine how Google Classroom enhanced English language learning in students' English at the Faculty of Literature and Humanities in the online learning system during the Covid-19 pandemic. This research was a classroom action research (CAR) conducted from March to July 2020. Classroom action research consists of four stages; planning, actions, observation, and reflection. It is better to fix this section as follows: The stage; teacher planning (preparation and pre-test), action (teaching by using Google Classroom), observation (Classroom observation), and reflection (personal reflection and post-test). The features of LMS Google Classroom promote the development of independent learners in which students can be triggered to access the information in any place and time. This research shows that the LMS Google Classroom learning model is considered an effective learning model to enhance independent learning. Data of the Speaking test has described in finding that there is significance increasing from pre-test to post-test. The score increased from 1103 in the pre-test to 1618 in the post-test. It shows an increase in mean score from 36.7667 in the pre-test to 54.1467 in the post-test. E-Learning is running well, especially for speaking classes. By using LMS Google Classroom in English teaching can help students to improve their English skills. Teaching English by implementing Learning Management System Google Classroom at the university can effectively improve students' English competency, where almost all students agree to this point. Twenty-five students agreed that this learning model could improve the students’ competencies, and only one student disagrees. For speaking teaching that some of the students disagree with using LMS Google Classroom, six students gave a negative response, and 24 agreed. The analysis results showed that the English Literature Study Program students at the Islamic University of Makassar responded well when their lecturer used LMS Google Classroom in the learning process.